(untitled) (CIPEEX, 2025)
Abstract: Prenatal care is a fundamental process to ensure maternal and neonatal health, involving strategies of health promotion, prevention of complications, and education. This study aimed to describe recommendations for the follow-up of low-risk prenatal care in primary health care. A qualitative and descriptive approach was conducted through a literature review using references from the Brazilian Ministry of Health and specialized textbooks in maternal and child health, with reflective analysis of the selected materials. The results showed that early diagnosis of pregnancy by physicians or nurses enables timely initiation of prenatal follow-up. Care involves periodic consultations, laboratory and imaging exams, detailed anamnesis, and physical and gyneco-obstetric evaluation, as well as guidance on vaccination, healthy lifestyle habits, and warning signs. Risk factors are classified into low and high complexity, defining the level of care required. The pregnant woman’s health booklet supports the registration of consultations, exams, and orientations, strengthening the bond between the woman and the health team. It was concluded that early and regular prenatal care, starting in the first trimester with at least six consultations, is essential to reduce maternal and neonatal complications. This process allows the identification of risk factors, planning of adequate care, and guidance on physical, psychological, and social changes during pregnancy, ensuring safety and quality in the follow-up of the mother-child dyad.